Immunoprofiling bronchoalveolar lavage cells reveals multifaceted smoking-associated immune dysfunction - Randall Smith; Sai Yendamuri; Yeshwanth Vedire; Spencer Rosario; Robert Zollo; Deschana Washington; Stephanie Sass; Nathaniel M. Ivanick; Mary Reid; Joseph Barbi (ERJ Open Research, 2023)
Background Bronchoalveolar lavage (BAL) is an underutilised tool in the search for pulmonary disease biomarkers. While leukocytes with effector and suppressor function play important roles in airway immunity and tumours, it remains unclear if frequencies and phenotypes of BAL leukocytes can be useful parameters in lung cancer studies and clinical trials. We therefore explored the utility of BAL leukocytes as a source of biomarkers interrogating the impact of smoking, a major lung cancer risk determinant, on pulmonary immunity. Methods In this “test case” observational study, BAL samples from 119 donors undergoing lung cancer screening and biopsy procedures were evaluated by conventional and spectral flow cytometry to exemplify the comprehensive immune analyses possible with this biospecimen. Proportions of major leukocyte populations and phenotypic markers levels were found. Multivariate linear rank sum analysis considering age, sex, cancer diagnosis and smoking status was performed. Results Significantly increased frequencies of myeloid-derived suppressor cells and PD-L1-expressing macrophages were found in current and former smokers compared to never-smokers. While cytotoxic CD8 T-cells and conventional CD4 helper T-cell frequencies were significantly reduced in current and former smokers, expression of immune checkpoints PD-1 and LAG-3 as well as Tregs proportions were increased. Lastly, the cellularity, viability and stability of several immune readouts under cryostorage suggested BAL samples are useful for correlative end-points in clinical trials. Conclusions Smoking is associated with heightened markers of immune dysfunction, readily assayable in BAL, that may reflect a permissive environment for cancer development and progression in the airway.